(untitled) (Journal of Monno Medical College, 2023)
Background: Diarrhoea is one of the major causes of morbidity and mortality among the under-five age group in Bangladesh. Effective by ORS treatment can reduce diarrhoea-related mortality and unnecessary hospitalization, for which role of mothers is important. The use of oral rehydration saline (ORS) is greatly affected by mothers’ knowledge and attitude towards using it in treating their children. Objectives: Assessment of the knowledge, attitude and practice of the mothers about ORS for better management of diarrhoea in children. Methodology: A cross-sectional descriptive study was carried out in the department of Paediatrics of Monno Medical College Hospital, Manikganj, during the period from January to December, 2022. Data were collected from 300 mothers by face-to-face interview by a questionnaire. Finally, collected data were analyzed, using SPSS software version 20. Results: Majority (195, 65.0%) of the children’s age were in between 6 month to 2 years. Most (143, 47.7%) of the mothers completed primary education. About two-thirds of the mothers (193, 64.3%) resided in rural areas. In this study, most (213, 71.0%) of the mothers always used ORS during the attack of diarrhoea, 281(93.7%) mothers had adequate knowledge about ORS, 253(84.3%) had knowledge about preparetion of ORS, 235(78.3%) informed to know when to administer ORS and 170 (56.7%) knew the exact amount of ORS to administer. Conclusion: Positive attitude was seen among the participant mothers regarding the use of ORS. But mothers’ knowledge and practices regarding its administration was insufficient. Journal of Monno Medical College, June 2023; 9 (1): 03-06